Direct Carbon Isotope Exchange Through Decarboxylative Carboxylation - Kingston, Cian (J Am Chem Soc, 2019)
A two-step degradation-reconstruction approach to the carbon-14 radiolabeling of alkyl carboxylic acids is presented. Simple activation via redox-active ester formation was followed by nickel-mediated decarboxylative carboxylation to afford a range of complex compounds with ample isotopic incorporations for drug metabolism and pharmacokinetic studies. The practicality and operational simplicity of the protocol was demonstrated by its use in an industrial carbon-14 radiolabeling setting.